Politically engaged but unwilling to protest: analyzing the role of authoritarian orientations and internet use on protest participation behavior - Saifuddin Ahmed (2023)
Several studies have investigated the effects of internet use on protest participation behavior. However, fewer have explored how personal dispositions of individuals moderate the impact of the internet. This study explores the relationship between political engagement, internet use, authoritarian orientation, and protest participation in Hong Kong, Taiwan, Thailand, and Myanmar. First, analysis of fourth-wave of the Asian Barometer survey data suggests a political engagement-driven stratification in protest participation across all settings. Second, internet use is positively associated with protest participation but only in authoritarian states, and citizens’ authoritarian orientation reduces the likelihood of protest action. Third, high authoritarian orientation subdues the participatory benefits of internet use for politically engaged citizens. Overall, the study confirms that politically engaged citizens are more capable of exploiting the benefits offered by the internet. Still, authoritarianism can inhibit the mobilizing potentials presented by the internet. The theoretical importance of attitudinal factors in protest participation is discussed.